Phenological shifts in hoverflies (Diptera: Syrphidae): linking measurement and mechanism - Hassall, Chris; Owen, Jennifer; Gilbert, Francis (Wiley, 2016)
An understanding of ecological and evolutionary responses to global environmental change requires both a robust measurement of the change that is occurring and a mechanistic framework for understanding the drivers of that change. Such a requirement provides a challenge because biological monitoring is often ad hoc, and mechanistic experiments are often performed under highly simplified conditions. This study integrates multiple datasets to evaluate our current knowledge of the measurement and mechanism of phenological shifts in a key pollinator taxon: the hoverflies (Diptera: Syrphidae). First, two large, complementary and independent monitoring datasets are used to test for trends in phenology: an ad hoc national recording scheme containing >620,000 records, and a standardised monitoring scheme with consistent methods over 30 years. Results show that ad hoc and standardised recording data give quantitatively the same value for phenological advance in hoverflies (ca. 12 days°C-1 on average at the beginning of the flight period), supporting the value of biological recording for the measurement of global ecological change. While the end of the flight period appears static in ad hoc recording, the standardised dataset suggests a similar advance as in the beginning of the flight period. Second, an extensive traits dataset and a novel database of laboratory-derived developmental data on Syrphidae (153 published studies) are used to test for mechanistic patterns in phenological shifts. The only species trait that influenced phenology was voltinism, where species with more generations per year exhibit stronger phenological advances. We demonstrate considerable variation in the laboratory-derived sensitivity to temperature but this does not match field-derived measures of phenology. The results demonstrate that, as for many taxa, we have a strong understanding of the patterns of global ecological change but that we currently lack a detailed mechanistic understanding of those processes despite extensive research into the fundamental biology of some taxonomic groups.